Students' citizenship competencies: The role of ethnic school composition and perceived teacher support. (2nd January 2022) - Sincer, Işıl; Volman, Monique; van der Veen, Ineke; Severiens, Sabine
ABSTRACT: The current study examined the effects of school ethnic composition and teacher-student relationships (teacher support) on students' citizenship competencies. Additionally, this study investigated the moderating effect of teacher support on the relationship between school ethnic composition and citizenship competencies. Citizenship was operationalized as competencies and knowledge concerning acting democratically, acting in a socially responsible manner, dealing with conflicts, and dealing with differences. Multilevel analyses among a sample of 4, 902 students from 75 Dutch secondary schools showed that the degree of school ethnic diversity is positively related to competencies in acting democratically, acting in a socially responsible manner, and dealing with differences, but it is negatively related to knowledge regarding acting in socially responsible manner and dealing with conflicts. Teacher support was positively associated with both competencies and knowledge in all social tasks. Except for one outcome, no moderation effect of teacher support was found.